The Indigenous State : Race, Politics, and Performance in Plurinational Bolivia - Postero, Nancy Grey (Book collections on Project MUSE., 2017)
"In 2005, Bolivians elected their first indigenous president, Evo Morales. Ushering in a new "democratic cultural revolution," Morales promised to overturn neoliberalism and inaugurate a new decolonized society. In this crucial new book, Nancy Postero examines the successes and failures in the ten years since Morales's election. While the Morales government has made many changes that have positively benefited Boliva's majority indigenous population, it has consolidated power and reinforced extractivist development models. In the process, indigeneity has been transformed from a site of emancipatory politics to a site of liberal nation-state building. By carefully tracing the political origins and practices of decolonization among activists, government administrators, and ordinary citizens, Postero makes an important contribution to our understanding of the meaning and impact of Bolivia's indigenous state."--Provided by publisher